Partial splenic embolization in beta-thalassemia major: a case report - Meral, Adalet; Sevinir, Betül; Sadıkoğlu, Yurtkuran; Nacarküçük, Ergun; Günay, Ünsal (The Turkish Journal of Pediatrics, 2000)
Partial splenic arterial embolization was performed in a thalassemic child for hypersplenism manifested by splenomegaly, leukopenia, thrombocytopenia, and anemia requiring frequent erythrocyte transfusion. During a follow-up period of 11 months, his hematological parameters improved significantly and the spleen size decreased. Partial splenic embolization could be an alternative therapy to surgical splenectomy for thalassemic children with hypersplenism.